Increasing Students' Critical Thinking Capacity: Bridging The Worlds Of Thought And Action - Banik, Lodia Amelia; Lelo, Kaleb; Nubatonis, Sonia M; Djami Manu, Kevin P; Seko, Sri N; Bili, Nadia F. M (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
It is important for students to understand their role in connecting thought and action, because this is an important foundation in achieving personal success. In response to this problem, the team of lecturers in the Philosophy of Science, Logic and Interpersonal Communication courses carried out PKM in the form of increasing the critical thinking capacity of students in the IAKN Kupang Pastoral Counseling and Christian Psychology Study Program through seminar activities with the theme